Development of plasma and whole blood taurine reference ranges and identification of dietary features associated with taurine deficiency and dilated cardiomyopathy in golden retrievers: A prospective, observational study - Ontiveros, Eric S.; Whelchel, Bradley D.; Yu, Joshua; Kaplan, Joanna L.; Sharpe, Ashley N.; Fousse, Samantha L.; Crofton, Amanda E.; Fascetti, Andrea J.; Stern, Joshua A. (PLOS ONE, 2020)
Introduction A surge in Food and Drug Administration (FDA) consumer complaints identified concerns that legume-rich, grain-free diets were associated with nutritionally-mediated dilated cardiomyopathy (DCM). Golden retrievers represent the most reported breed affected by this condition and previous studies documented the disease is responsive to dietary change and taurine supplementation. Although dietary findings across cases are compelling, prospective studies with control groups are lacking. The role of diet in developing taurine deficiency and echocardiographic changes consistent with DCM in healthy dogs is unknown. Objectives We hypothesized that golden retrievers eating non-traditional diets are at a higher risk of having taurine deficiency and nutritionally-mediated DCM compared with those eating traditional commercial diets. We aimed to compare taurine concentrations and echocardiographic indices of systolic function between golden retrievers in each diet group and elucidate associations between diet and these variables. Additionally, we aimed to generate breed-specific reference intervals for whole blood and plasma taurine concentrations. Animals 86 golden retrievers. Methods Golden retrievers eating traditional or non-traditional diets were evaluated and diet history, taurine concentrations and echocardiographic data were collected. Dietary features, taurine concentrations and echocardiographic findings were compared between diet groups. Relative risks were calculated for the likelihood of echocardiographic abnormalities and taurine deficiency in each diet group. Breed-specific reference intervals were constructed for taurine concentrations in dogs from the traditional diet group. Results Golden retrievers eating non-traditional diets had significantly lower taurine concentrations and more frequent systolic dysfunction. Breed specific reference intervals are higher than previously reported across breeds. Conclusions Non-traditional diets, which were typically grain-free and contained legumes in this study, were significantly associated with and have increased relative risk for the identification of taurine deficiency and echocardiographic abnormalities consistent with nutritionally-mediated DCM. These findings were identifiable in the absence of clinical signs and support the findings of multiple previous studies and the ongoing FDA investigation.